Bakteri Pendegradasi Amonia Limbah Cair Karet Pontianak Kalimantan Barat - Masnur Turnip, Tetty Afrianti Nainggolan, Siti Khotimah, (Universitas Tanjungpura, 2015)
Liquid waste from rubber processing factories contains natural bacteria that degrade ammonia which can be used in the process of treatment of liquid waste of rubber and is capable of oxidizing ammonia. This research aimed to reveal the genera of bacteria that degrade ammonia derived from liquid waste of rubber that was taken from the rubber industry factory PT. Sumber Djantin. The research was conducted in a period of 4 months, from July to October 2014. The bacteria were isolated using the pour plate method, then their morphology was observed macroscopically, microscopically, and in addition, biochemical tests were performed. The identification of bacterial isolates referred to Bergey's Manual of Determinative Bacteriology. A total of seven genera of bacteria found in the liquid waste from rubber factory PT. Sumber Djantin. The seven genere of bacteria were Nitrosomonas, Nitrosolobus, Nitrosospira, Nitrosococcus,Nitrospina, Nitrospira, and Nitrococcus. All are classified into the group of gram-negative bacteria.